Hoping in Nature: Pragmatic Hope and Spirituality - Shade, Patrick (Research in the social scientific study of religion, 2010)
a pragmatic view of hope emphasizes the habits we possess as natural organisms. As such, it provides a context in which to address spiritual matters without inviting conflict with the findings of science or our ordinary practices. i argue that a pragmatic approach to hope and spirituality enables us to discern degrees of spirituality in the process of hoping, thereby explaining the close connection between the two and helping us render that connection more meaningful and pervasive.